Between Natural Tourism, the Booming of Laskar Pelangi Film, and the Image of Environmental Damage: Measuring the Perception of Regional Tourist on Bangka Belitung Tourism. (November 2019) - Ibrahim, I; Zukhri, N; Rendy, R
Abstract: Image, impression, and tourist information sources are three important things to be explored in tourism development. Bangka Belitung which in the last few years has been trying to promote the economic sector based on post-tin and plantation tourism dealing with preparedness in management. This study wants to find out how tourists perceive Bangka Belitung, related to the tourist destinations, general views of tourists, and what issues are important to be considered by stakeholders. The study was designed to measure the perceptions of tourists from outside the area in looking at Bangka Belitung on the tourist side based on a quantitative design with a survey model. This research found that visitor arrivals to Bangka Belitung are basically planned as holiday trips from the beginning, not incidental trips. Another thing that was found is that the initial negative impression that emerged in general was environmental damage and the impression of a quiet area. The study also found that information sources for tourists in general are still conventionally based, namely relying on information from friends or family, not yet using a social media or technology base. It was also found the fact that culinary and historical visits have not become an important magnet in the planning of tourists' trips. In the end, this study found the tendency to visit tourist destinations based on natural beauty, but it is somewhat different from Bangka, tourists in Belitung tend to visit more varied places as an implication of the popular Laskar Pelangi Film. The study concluded that at least the issues that were important as weaknesses were still felt by visitors, including limited transportation, facilities at tourist sites visited that were still minimal, local government support that was considered not optimal, and environmental damage that was considered to be potential for disrupting tourism.